Analysis of the cost recovery rate for inpatient services under the national health insurance scheme at hospital X in Yogyakarta - Hafni, Diska Arliena; Aji, Seto Satriyo Bayu; Andriani, Monika (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to analyze the cost recovery rate of inpatients under the National Health Insurance (NHI) program at Hospital X in Yogyakarta. Design/Methodology/Approach: This study employed an explanatory sequential mixed-methods design using a case study approach. The cases to be examined involved NHI inpatient patients in the Respiratory, Cardiology, and Obstetrics-Gynecology departments. Data will be analyzed using the Cost Recovery Rate (CRR) formula.Research findings: The CRR for inpatient NHI patients at the Respiratory Clinic shows a CRR value of 143%, while the CRR values for the Cardiology, Obstetrics, and Gynecology Clinics are 95% and 80%, respectively. Cross subsidization from clinics with positive CRR values can be implemented to ensure that the hospital's Revenue from Social Security Agency for Health (SSAH) claims remains positive overall. Theoretical contribution/ Originality: This research has made a valuable contribution to the accounting literature on hospital entities, a field that remains significantly underexplored. Practitioner/Policy implication: The findings of this research can serve as a valuable asset for hospitals and the government in formulating policies that promote the enhancement of equitable and sustainable healthcare services for stakeholders.Research limitation/Implication: The limitation of this study is that it only examined the CRR values of inpatient NHI patients in a single hospital, focusing exclusively on inpatients in the NHI Respiratory, Cardiology, and Obstetrics and Gynecology departments.